The Role of Emotion Regulation on Compulsive Shopping of Clothing - Djudiyah Djudiah (Psikostudia : Jurnal Psikologi, 2022)
During the Covid-19 pandemic, almost all student activities are carried out from home, whether for lectures, shopping, etc. The number of activities carried out at home for a long period has resulted in students feeling bored/bored and feeling pressured by their routine activities. They seek entertainment by looking at the products offered in online store outlets. This can encourage students to spend excessively or compulsively, especially for students who are less able to regulate emotions. This study aims to empirically prove the effect of emotion regulation on compulsive shopping and wants to know the dimensions of emotional regulation inability that support students' compulsive spending. This study uses a quantitative approach. The subjects of this study amounted to 166 active students of the Faculty of Psychology, University of Muhammadiyah Malang. The data collection methods used were the Difficulties in Emotion Regulation Scale (DERS) and the compulsive shopping scale for clothing. Data analysis was performed using the regression analysis method with the help of the SPSS version 21 program. The results of the analysis showed that there was an influence of emotion regulation on compulsive clothing shopping. The dimensions of difficulty controlling impulses and refusing to realize emotions are dimensions of the inability to regulate emotions that play a major role in compulsive shopping for clothes. Di masa pandemi Covid 19 ini hampir semua aktivitas mahasiswa dilakukan dari rumah, baik untuk aktivitas perkuliahan, berbelanja, dll. Banyaknya aktivitas yang dilakukan dilakukan di rumah dalah kurun waktu yang cukup lama ini mengakibatkan mahasiswa merasa jenuh/bosan dan merasa tertekan dengan aktivitas-aktivitas rutinnya. Mereka mencari hiburan dengan melihat-lihat produk yang ditawarkan di gerai toko online. Hal ini dapat mendorong mahasiswa untuk melakukan pembelanjaan secara berlebihan atau kompulsif terutama pada mahasiswa yang kurang mampu melakukan regulasi emosi. Penelitian ini bertujuan untuk membuktikan secara empiris pengaruh regulasi emosi terhadap belanja kompulsif dan ingin mengetahui dimensi ketidakmampuan regulasi emosi yang mendukung pembelanjaan kompulsif mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian ini berjumlah 166 mahasiswa aktif Fakultas Psikologi Universitas Muhammadiyah Malang. Metode pengumpul data yang digunakan adalah skala Difficulties in Emotion Regulation Scale (DERS) dan skala belanja kompulsif pakaian.  Analisis data dilakukan dengan metode analisis regresi dengan bantuan program SPSS versi 21. Hasil analisis menunjukkan bahwa ada pengaruh regulasi emosi terhadap pembelanjaan kompulsif pakaian. Dimensi kesulitan mengontrol impuls dan menolak menyadari emosi merupakan dimensi ketidakmampuan melakukan regulasi emosi yang berperan besar terhadap belanja kompulsif pakaian.